Motor development in six to seven year old children with identified intrinsic barriers to learning: a cross-sectional study - Marsh, Richard (My University, 2017)
Background: Research has proven that conditions such as developmental coordination disorder (DCD) and attention deficit hyperactivity disorder (ADHD) are becoming more prevalent in children of school going age and that children presenting with these conditions have intrinsic barriers to learning. ADHD has been found in 3-5% of children. A 2001 census in South Africa showed 12% of the population had intellectual disabilities and 7% communication problems. A 2011 South African census show 3, 2% of the South African population aged five and above has mild concentration/remembering difficulties. When a child has poor performance, this can cause low self-esteem, poor social functioning, risk of obesity and vascular disease. The comorbidity between DCD and ADHD has been considered at a rate of 50%. Aim: The aim of this study was to determine whether children with intrinsic barriers to learning have specific motor development deficits. Method: There were 27 participants assessed using the Movement Assessment Battery for Children second version (M-ABC 2). The children were recruited from a private remedial school in Honeydew, South Africa and were identified as having intrinsic barriers to learning. The assessment looked at Aiming and Catching, Balance and Manual Dexterity. Each participant was assessed once. These results were analysed by looking at the prominent deficit and correlation to demographics or conditions. An ANOVA analysis was done to compare the different between conditions to Aiming and Catching, Balance and Manual Dexterity. Results: There were 10 females and 17 male children enrolled in the study. The mean age was seven years three months and fourteen days. The standard deviation of age was ±140.6 days. The most common diagnosis was ADHD (48%) followed by speech problems (33%). The Manual Dexterity mean score was 7.82 (± 2.22), the Aiming and Catching mean score was 9.78 (± 3.28) and the Balance mean score was 7.59 (± 2.91). The total mean score for the M-ABC was 7.63 (± 2.84). Manual dexterity and Balance scores were both significantly lower than the Aiming and Catching scores (p=0.02 and p=0.01, respectively). The results indicated no significant difference between the Manual Dexterity and Balance scores (p= 0.55). The ANOVA analysis showed that children with speech problems scored slightly higher in Manual Dexterity than children with anxiety problems and processing problems but this difference was not significant (p=0.52). Children with ADHD and speech problems appeared to score slightly higher in Aiming and Catching than children with anxiety problems and processing problems but this was not significantly different (p=0.15). Children with processing problems scored significantly higher (p=0.03) in Balance than children with the other conditions. Conclusion: Children who have intrinsic barriers to learning have been recognised to have motor deficits that fall into the diagnosis of DCD. It is important to assess these children to optimise their intervention program; not just from a cognitive aspect but from a motor aspect as well. The results of this study found that Manual Dexterity and Balance are motor components that were the most affected. Addressing these aspects may help improve the activity levels and participation of these children.
A research report submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science (Physiotherapy) Johannesburg, 2017.
Keywords: Anatomy; Physiology